That deserves a wow : untold stories of legends and champions, their wins and heartbreaks - Myers, Chris, 1959-; Thrasher, Travis, 1971- (William Morrow, an imprint of HarperCollins Publishers, 2024)
"Emmy Award-winning broadcaster Chris Myers reflects on his illustrious career as one of the most trusted and renowned journalists in sports. Myers has witnessed and participated in his fair share of historic events: on the field when the earthquake struck the 1989 World Series; on the air throughout the tragic aftermath of the 1996 Atlanta Olympics bombing; on the sidelines during the Patriots' stunning comeback at Super Bowl LI; and a contentious live interview with the notorious OJ Simpson. Now Myers offers an inside look at all these moments and more, revealing the joys and pressures of working with the world's most famous athletes and sharing the experiences and interactions that never made it on screen. He takes readers behind the scenes with the biggest names in sports, including Mike Tyson, Muhammed Ali, Tom Brady, John Wooden, Bill Belichick, Charles Barkley, Barry Bonds, Serena Williams, Jack Nicklaus, Pete Sampras, and even Bill Murray. Through it all, Chris captures a community that is bigger than sports, one that has banded together through triumph and tragedy, providing lessons about excellence, compassion, and connection"--